Gender and landscape : renegotiating morality and space - Dowler, Lorraine; Carubia, Josephine; Szczygiel, Bonj (Routledge, 2005)
Annotation Gender and Landscape is a feminist inquiry into a long-ignored area of study: the landscape. Although there has been an exhaustive investigation into issues of gender as they intersect with space and place, very little has been written about the gendering of the landscape. This volume provides a bridge between feminist discussions of space and place as something 'lived' and landscape interpretations as something 'viewed'.
Keywords: Feminism.; Landscapes.; Féminisme.; Paysages.; feminism.; landscapes (environments); SOCIAL SCIENCE -- Feminism & Feminist Theory.; Feminism; Landscapes